Body weight, haematological indices and intestinal morphometric of broilers provided with diets containing formic acid, butyric acid or their blends - Isroli, I.; Murwani, R.; Yudiarti, T.; Widiastuti, E.; Wahyuni, H. I.; Sartono, T. A.; Sugiharto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
The study investigated the influence of dietary incorporation of formic acid, butyric acid or their blends on growth rate, haematological indices and intestinal morphometric of broilers. A number of 240 Lohmann MB-202 chicks were pass rounded to four dietary groups, including CONT (chicks taking in basal feed with no additive), BTRT (chicks receiving basal feed with 0.03% butyric acid), FRMT (chicks receiving basal feed with 0.1% formic acid) and BTRT+FRMT (chicks receiving basal feed containing 0.03% butyric acid and 0.1% formic acid). Weight of chicks and intake were measured every week, while blood sample was collected at day 21 and 35. At day 35, birds were slaughtered and small intestinal segments and digesta were collected. At day 21, body weight was bigger (P<0.05) in BTRT+FRMT than in other birds. Feeding the blends of formic and butyric acids resulted in higher (P<0.05) value of mean corpuscular haemoglobin concentration (MCHC) at day 21. Feeding organic acids was associated with the lower (P<0.05) proportion of thrombocytes in broilers at day 35. Supplementation of butyric acid resulted in higher (P<0.05) serum albumin concentration at day 35. Butyric acid produced higher (P<0.05) levels of triglyceride as well as low-density lipoprotein (LDL) in the serum. The mixture of formic and butyric acids resulted in higher (P<0.05) titer of antibody against Newcastle disease vaccine (NDV) at day 21. Feeding formic acid decreased (P<0.05) ileal population of lactose negative enterobacteria at day 35. Overall, dietary supplementation of the blends of formic and butyric acids resulted in improved growth and immune defence of broiler chicks.